Reynolds portraiture in action - Hallett, Mark 1965- (Published for Paul Mellon Centre for Studies in British Art by Yale University Press, 2014)
"A deeply researched and elegantly written study on Sir Joshua Reynolds (1723-1792)-- Georgian England's most celebrated portraitist and the first president of the British Royal Academy of Arts-- this invaluable volume explores all aspects of Reynolds's portraiture. Mark Hallett provides detailed, compelling readings of Reynolds's most celebrated and striking works, investigating the ways in which they were appreciated and understood in his own lifetime. Recovering the artist's dynamic interaction with his sitters and patrons, and revealing the dramatic impact of his portraits within the burgeoning exhibition culture of late-eighteenth-century London, Hallett also unearths the intimate relationship between Reynolds's paintings and graphic art. Reynolds: portraiture in action offers a new understanding of the artist's career within the extremely competitive London art world and takes readers into the engrossing debates and controversies that captivated the city and its artists"--Publisher's description